Miniaturized branch-line coupler based on slow-wave microstrip lines. Issue 10 (22nd August 2018) - Alhalabi, H.; Issa, H.; Pistono, E.; Kaddour, D.; Podevin, F.; Abouchahine, S.; Ferrari, P.
Abstract: This paper presents a miniaturized 3-dB branch-line coupler based on slow-wave microstrip transmission lines. The miniaturized coupler operating at 2.45 GHz is designed and implemented on a double-layer printed circuit board substrate with blind metallic vias embedded in the lower substrate layer providing the slow-wave effect. Based on this concept, a 43% size miniaturization is achieved as compared with a classical microstrip branch-line coupler prototype. The measured S parameters present a return loss of 25.5 dB and an average insertion loss equal to 0.05 dB at the operating frequency.